Clinical Phenotype and Outcomes of Indo-Asian Patients with ANCA-Associated Glomerulonephritis in the North West, UK - Lauren Floyd; Joshua Storrar; Sanjeev Pramanik; Adam D. Morris; Smeeta Sinha; Silke R. Brix; Philip A. Kalra; Ajay P. Dhaygude (MDPI AG, 2023)
ANCA-associated vasculitides (AAV) are rare, autoimmune conditions associated with end-stage kidney disease (ESKD) and mortality. Data have predominately been from White populations of European ancestry although geographical differences are well documented. Few studies have looked at the incidence, phenotype and clinical outcomes of ethnic minority patients, in particular Indo-Asian populations. A two-center, retrospective cohort study was conducted of patients with ANCA-associated glomerulonephritis (AAGN), self-identifying as Indo-Asian in the North West, UK between 2009 and 2023. A control group of White patients was identified from the same databases and recruited consecutively in relation to the original cohort of Indo-Asian patients. A total of 66 patients were included, 24 patients of Indo-Asian ethnicity and a control cohort of 42 patients of White ethnicity. Indo-Asian patients had a lower median age at diagnosis (53.0 vs. 57.5 years, p = 0.15) and there was an increased prevalence of diabetes mellitus (33.3% vs. 4.8%, p = 0.002) and a higher incidence of previous TB exposure (12.5% vs. 0%, p = 0.019). Outcomes including relapse, ESKD and mortality were similar. We demonstrated an increased crude incidence of AAGN in Indo-Asian patients in the UK compared to similar epidemiological studies. Consideration needs to be given to epidemiological and genetic research, achieved by collaboration and broader recruitment in clinical trials.